Penerapan Metode Multi Criteria Decision Making Untuk Menentukan Handphone Android 4G Low-End - Heru Purwanto; Ahmad Fauzi; Achmad Sumbaryadi (LPPM Universitas Bina Sarana Informatika, 2021)
Since the outbreak of the Covid-19 pandemic, there have been adjustments in teaching and learning activities. Learning is not done in schools to avoid potential dangers to transmission of the corona virus. There are many obstacles faced by teachers, students and parents in distance learning activities. Mobile is one of the basic needs to support learning activities, families with more than one child will experience difficulties when having to do tasks simultaneously if they only have a cellphone. The purpose of this study is to provide a solution in the form of selecting low end 4G Android phones at affordable prices. Application of the Multycriteria Analytical Hirarchi Process (AHP) method with the criteria of Specifications, Price and Design. Selection of alternative three mobile phones, namely Samsung A10s, Vivo Y12 and Realme 5 makes it easier for students to choose according to their needs. Data collection of 45 samples was carried out through distributing questionnaires with google form and offline. The results of the calculation of Vivo Y12 = 0.23, Samsung A10s = 0.30 and Realme5 = 0.47